Pengaruh Pijat Bayi untuk Mengur Pengaruh Pijat Bayi untuk Mengurangi Kembung pada Bayi Usia 0-12 Bulan - Asti Andriyani, Andriyani (JURNAL KEBIDANAN BESTARI, 2026)
Infant bloating is a condition characterized by the accumulation of gas in the gastrointestinal tract, resulting in abdominal fullness, distension, or firmness. This condition may occur in both infants and adults. One of the non-pharmacological interventions commonly used to alleviate bloating is infant massage. Infant massage is a therapeutic technique involving gentle, rhythmic stroking and manipulation of an infant's body using the hands or appropriate massage tools. It is intended to provide both physical and emotional stimulation that supports optimal growth and development. This study aimed to evaluate the effect of infant massage on reducing complaints of bloating in infants aged 0–12 months. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. The study included 26 participants selected through purposive sampling. Data were collected using interviews and observation checklists and were analyzed using the Wilcoxon signed-rank test. The results indicated that the majority of infants were five months old (4 participants, 15.4%), while the most common body weight was 7 kg (11 participants, 42.3%). Statistical analysis demonstrated a significant reduction in bloating complaints following the intervention, with a Wilcoxon test p-value of 0.000 (p < 0.05). These findings indicate that infant massage has a statistically significant effect on reducing bloating complaints in infants aged 0–12 months. It can therefore be concluded that infant massage is an effective non-pharmacological intervention for relieving bloating symptoms in this population